The Toponomastic Primer: Basic Terminology and Field Research Methodology - Skračić, Vladimir (2025)
Developing a consistent onomastic terminology in the Croatian language was precisely the task to which Vladimir Skračić devoted himself wholeheartedly just before retiring, attempting to systematize what he described in the preface as a “considerable mess in our discipline.” While retaining already established terms, which could be said to belong to the so-called core terminology, the author proposed a comparatively large number of new ones. The problem with the latter group is clear: how to translate terms for which there are no direct equivalents in English-language onomastic terminology, or where such equivalents exist but are not widely accepted? Yet even terms from the former group posed difficulties. For instance, following Croatian tradition, for Skračić, the term zoonym is reserved for particular species rather than names of individual animals, whereas in the terminology of the International Council of Onomastic Sciences, the term covers “proper name of an animal.” During our discussions, the translator, Tomislav Kuzmanović, insisted – and I am glad he did – that the onomastic terminology presented in this book constitutes a well-thought-out system, and that any hybrid translation solutions would significantly compromise the clarity and consistency of the text. Therefore, all onomastic terms from the original were ultimately retained in the translation, all formed using the Greek stem + -onym model, with adaptations in accordance with the rules for romanizing Greek words in English. There is no doubt that this choice by the translator and the editor will not meet with universal approval. However, all terms are thoroughly explained, so readers encountering them for the first time should have no difficulty understanding them.With the author’s approval, some minor errors from the original were corrected during translation. The author also updated the overview in Chapter 2.2. to reflect changes in the status of island and coastal toponymy research in the fourteen years since the original publication.